SYSTEMATIC LITERATURE REVIEW: PENGARUH APLIKASI LAYANAN PESAN ANTAR MAKANAN TERHADAP MINAT BELI KONSUMEN - Alam, Hanifah Pagar; Haludin, Guntur; Adillah, Meylia; Anggrayni, Vidiyana; Rosalia, Tita (MANAJEMEN DEWANTARA, 2024)
The food delivery service application is a platform that provides services for people to order and buy food or drinks online. Delivery service applications such as GoFood, GrabFood, and ShopeeFood makes it easy for consumers to order food without having to visit the restaurant. Not only does it make it easy to order and purchase food, but the delivery service application also provides a variety of menu and restaurant choices. This research aims to identify factors that influence consumer purchase intention in food delivery service applications. Using qualitative methods with an approach Systematic Literature Review (SLR), this research analyzes articles related to the influence of food delivery service applications on purchase intention. The study results show that factors that are significant in attracting consumer purchase intention include speed of delivery, menu variations, ease of ordering, payment, display of product photos, user reviews, perceived ease of use, brand image, price and product quality